2023
DOI: 10.1515/bot-2022-0061
|View full text |Cite
|
Sign up to set email alerts
|

From Tasmania to the world: long and strong traditions in seaweed use, research, and development

Abstract: Tasmania is an island state in south-eastern Australia that has a long and rich history of seaweed use, research, and development. It is a cool-temperate system with 750 macroalgal species currently described. Tasmanian Aboriginal peoples have lived on this land for at least 40,000 years utilising seaweed as food, shelter, water carriers and medicine, as well as for ceremonial reasons. Modern taxonomic investigations began with French naturalist Jacques-Julien Houtou de La Billardière in 1791, and there are 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 183 publications
0
10
0
Order By: Relevance
“…It is possible that L. corrugata could become extinct or severely limited in distribution by 2100, particularly as it is at its geographic limit in Tasmania, as there is no suitable habitat (i.e., shallow rocky reef) further south. Indeed, largescale declines in L. corrugata populations have already occurred along Tasmania's coasts with >30% declines between 2008 and 2018 (Mellin et al., 2021); however, due to the lack of historical data and monitoring, the full extent of their decline is unknown (Hurd et al., 2023). Certainly, ocean warming in Tasmania has already led to extreme declines of another kelp, Macrocystis pyrifera , which has a similar thermal range to L. corrugata (Butler et al., 2020; Layton & Johnson, 2021; Schiel & Foster, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that L. corrugata could become extinct or severely limited in distribution by 2100, particularly as it is at its geographic limit in Tasmania, as there is no suitable habitat (i.e., shallow rocky reef) further south. Indeed, largescale declines in L. corrugata populations have already occurred along Tasmania's coasts with >30% declines between 2008 and 2018 (Mellin et al., 2021); however, due to the lack of historical data and monitoring, the full extent of their decline is unknown (Hurd et al., 2023). Certainly, ocean warming in Tasmania has already led to extreme declines of another kelp, Macrocystis pyrifera , which has a similar thermal range to L. corrugata (Butler et al., 2020; Layton & Johnson, 2021; Schiel & Foster, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This raises concerns for the future of this unique, endemic species, as they appear to be highly sensitive to relatively small increases in temperature. It is possible that the species will be at an extinction risk if ocean warming continues at the current rate, with subsequent effects on entire ecosystems and the communities the kelp supports, which themselves have been almost completely unstudied (Hurd et al., 2023; Nardelli, Visch, Wright, et al., 2023). Moreover, recent studies have shown 100% mortality rates of farmed L. corrugata during summer (Nardelli, Visch, Farrington, et al., 2023); the narrow thermal range identified in our study further suggests that L. corrugata may not be suitable for aquaculture in a future, warmer ocean, particularly as temperatures are already reaching close to their thermal limits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seasonal growth patterns of the red seaweeds Lenormandia marginata , Plocamium cirrhosum , Hemineura frondosa , Delisea plumosa , and Schottera nicaeensis have not been previously studied (Hurd et al, 2023). Therefore, the drivers of DOC release are considered based solely on their nitrogen status.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of spatial and temporal variability in zoospore quality and gametophyte development in E. radiata therefore remains a knowledge gap. Closing this gap will clarify the impacts of global warming on early life stages of this habitat‐forming species in Tasmania and enable more accurate predictions of growth and distribution through modeling (Assis et al., 2016; Castro et al., 2020; Davis et al., 2022; Franco et al., 2018; Hurd et al., 2023).…”
Section: Introductionmentioning
confidence: 99%